“To Make Peace”. On Symbols and Monuments: Constructing the Syncretic Museum (Clepsidra - Interdisciplinary Journal of Memory Studies, 2022)
This article analyses the process of construction of public memory of Spanish State’s past of war and dictatorship, In doing so, it demonstrates how State has generated symbo- lic expressions and rituals to establish a syncretic memory, supported by a narrative of parity whose more emblematic example is the Monument of the Deads, the 2nd of may 1808. In this sense, the paper examines the ethical-political bases of Spanish State.
Keywords: Franco Ìs Dictatorship; Democratic Memory; Heritage; Symbolic System; Reconciliation.